Host-pathogen interactions between the skin and Staphylococcus aureus - Krishna, Sheila (2011)
Staphylococcus aureus is responsible for the vast majority of bacterial skin infections in humans. The propensity for S. aureus to infect skin involves a balance between cutaneous immune defense mechanisms and virulence factors of the pathogen. The tissue architecture of the skin is different than other epithelia especially since it possesses a corneal layer, which is an important barrier that protects against the pathogenic microorganisms in the environment. The skin surface, epidermis and dermis each contribute to host defense against S. aureus. Conversely, S. aureus utilizes various mechanisms to evade these host defenses to promote colonization and infection of the skin. This review will focus on host-pathogen interactions at the skin interface during the pathogenesis of S. aureus colonization and infection.